Melatonin Promotes Yield Increase in Wheat by Regulating Its Antioxidant System and Growth Under Drought Stress - Xue Li; Jia Liu; Cuiping Zhang; Ze Liu; Xiang Guo; Shaoxiang Li; Hongsheng Li; Kun Liu; Kunzhi Li; Mingliang Ding (Biology)
Drought stress constitutes a major challenge to wheat production. Melatonin plays a vital role in plants’ resistance to drought stress. Nevertheless, the influence of melatonin seed coating on the drought resistance ability of wheat remains unclear. Hence, in this study, wheat (Yunmai 112) was chosen as the experimental material. The research results indicated that 100 µM exogenous melatonin treatment enhanced the germination rate of wheat seeds by 11% compared to the CK group. Melatonin seed coating (100 or 200 µM) significantly inhibited the accumulation of ROS in wheat seedlings under drought stress conditions and facilitated the growth of wheat seedlings. Then, 100 µM melatonin seed coating elevated the activity of antioxidant enzymes (CAT, Cu/Zn-SOD, POD, and T-GSH) in wheat seedlings and strengthened the resistance of wheat to drought stress. In contrast to the control, 100 or 200 µM melatonin seed coating significantly raised the contents of soluble protein and chlorophyll in wheat seedlings. Further studies demonstrated that 100 µM melatonin seed coating promoted the increase in the thousand-grain weight and yield of wheat under drought stress. Taking together, melatonin seed coating is an effective approach for enhancing the stress resistance and the yield of wheat under drought stress.